2016
DOI: 10.1021/acs.chemrestox.6b00099
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Fragment-Based in Silico Profiler for Michael Addition Thiol Reactivity

Abstract: The Adverse Outcome Pathway (AOP) paradigm details the existing knowledge that links the initial interaction between a chemical and a biological system, termed the molecular initiating event (MIE), through a series of intermediate events, to an adverse effect. An important example of a well-defined MIE is the formation of a covalent bond between a biological nucleophile and electrophilic compound. This particular MIE has been associated with various toxicological endpoints such as acute aquatic toxicity, skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 26 publications
(36 reference statements)
2
34
0
Order By: Relevance
“…More notably, in either scheme, the addition reaction is more favorable in a polar environment (high dielectric constants) 45 , especially in basic buffer that facilitates producing the thiolate group. 35 This makes sense as the high dielectric constant increases the dielectric screen between the general acid and the general base leading to the charge localization of the reaction groups. Thus, the transition state is further stabilized and the energy barrier reduced.…”
Section: Resultsmentioning
confidence: 99%
“…More notably, in either scheme, the addition reaction is more favorable in a polar environment (high dielectric constants) 45 , especially in basic buffer that facilitates producing the thiolate group. 35 This makes sense as the high dielectric constant increases the dielectric screen between the general acid and the general base leading to the charge localization of the reaction groups. Thus, the transition state is further stabilized and the energy barrier reduced.…”
Section: Resultsmentioning
confidence: 99%
“…In doing this it is possible to calculate the energy difference between the reactants and transition states and/or intermediate structures computationally, this is termed the activation energy (Eact). Previous studies have shown calculated Eact to correlate well with reaction rate for Michael acceptors [11,12,14,19,20].…”
Section: Introductionmentioning
confidence: 87%
“…A recent study by the current authors showed it was possible to predict experimental reactivity (expressed as pRC50 values) for a set of Michael acceptors using a fragment-based in silico profiler where fragments are stored in a database with their respective, pre-calculated activated energy (Eact) values [20]. Fragments were developed for Michael acceptors by defining the length of alkyl chain beyond which further increases in chain length failed to significantly increase Eact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the new additions to the COSMOS NG is the ability to profile and group compounds by categories and pathways. Well-known chemical categories or mode-of-action (MoA) chemotypes are available for mutagenesis [66] , genotoxic carcinogens [67] , [68] , DNA binders [69] , [70] , [71] , protein binders [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , liver toxicity [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] and DART structural rules [88] . If the structure matches any of the categories defined by chemotype fragment, the structure will be associated with particular categories or rules.…”
Section: The Potential Role Of Cosmos Ng Within a Knowledge Hubmentioning
confidence: 99%